KARAKTERISTIK FISIK DAN ANTIMIKROBA EDIBLE FILM DARI PATI TALAS BENENG, KITOSAN DAN MINYAK ATSIRI JAHE MERAH - Kusuma, Azahra Wibi; Yuniarti, Rahma; Nabila, Firyal Giani; Rahmayanti, Diana; Meindrawan, Bayu (Jurnal Sains dan Teknologi Pangan, 2023)
The existence of synthetic packaging that can damage the environment has encouraged various research on biodegradable edible films. Edible films can be formulated from beneng taro starch combined with chitosan and red ginger essential oil which can improve physical performance and antimicrobial capabilities. The results of this research show that the addition of ginger essential oil to beneng-chitosan taro starch-based edible film influences thickness, mechanical properties (tensile strength and elongation), water vapor transmission rate, color and antimicrobial activity. The edible film formulation of beneng taro starch, chitosan and 2% ginger essential oil is the best formulation with thickness of 0.0283 mm, elongation of 81.52 mm, water vapor transmission rate of 12.02 g/hour m2, diameter of the inhibition zone against S. aureus 1 .16 mm and E. Coli 9.50 mm. The resulting edible film has the potential to be used as antimicrobial food packaging.